Islamic Religious Learning for Muallaf at Pesantren - Siregar, Hariman Surya; Mohd Nor, Mohd Roslan; Hajrullah, Hajrullah (Jurnal Pendidikan Islam, 2020)
This study aims to describe the learning activities of Islamic Religious Education at the An-Naba Islamic Boarding School for muallaf. This research used a qualitative approach with a descriptive analytic method. Interviews, observation and documentation were applied to collect the data. Data were analyzed using the Milles and Huberman model analysis. The results showed that learning Islam for muallaf has the objectives to improve the quality of learning, create an ideal Muslim personality, foster Muslim morals, Muslim salimah personalities, and Muslims as caliphs. The optimization program for Islamic religious learning consists of a coaching program, an educational program, a development program, and a vocational education development program. The process of organizing Islamic religious learning for muallaf consists of four stages: shahâdah (the process of Islamization); ta'âruf (introduction) and tafâhum (understanding); ibthan (internalization); and muwâfaqah (acceptance).